The Role of Libraries in Increasing Early Childhood Interest in Reading in the Tangerang Regency Area - Alifa Savira; Al Faruq Abdullah, Muhamad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The Pembina State Kindergarten Library plays an important role in developing students' love of reading. The activity that will be developed is library science, with library science. Pembina State Kindergarten can stimulate children's interest in reading. Literacy activities developed by the library include borrowing and returning books, telling stories, and reading to children. Pembina State Kindergarten students take turns observing three activities that help Pembina State Kindergarten students develop a love of reading. Children read books, they need to read. While reading; interested in reading; I always wanted to read and monitor (read monitor).The Pembina State Kindergarten Library plays an important role in developing students' love of reading. The activity that will be developed is library science, with library science. Pembina State Kindergarten can stimulate children's interest in reading. Literacy activities developed by the library include borrowing and returning books, telling stories, and reading to children. Pembina State Kindergarten students take turns observing three activities that help Pembina State Kindergarten students develop a love of reading. Children read books, they need to read. While reading; interested in reading; I always wanted to read and monitor (read monitor).